2016
DOI: 10.1111/pcn.12412
|View full text |Cite
|
Sign up to set email alerts
|

Serum copeptin in children exposed to maltreatment

Abstract: CM is associated with copeptin serum levels independently of age, sex, and symptom severity. Copeptin is a promising new biomarker for children with a history of abuse and/or neglect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 48 publications
2
21
2
2
Order By: Relevance
“…In a further study, induction of panic symptoms in 30 healthy male human subjects by intravenous cholecystokinin-tetra peptide, a substance well known to induce panic symptoms and activate the pituitary-adrenal axis activity, resulted in substantial increases in circulating concentrations of copeptin and cortisol [37]. Further, children exposed to maltreatment, such as physical abuse, neglect, emotional maltreatment and sexual abuse, and individuals with suicidal behaviour have higher circulating copeptin concentrations [10,13]. Finally, although depressed ambulatory patients, participating in an exercise study, had similar plasma copeptin concentrations to controls [36], among individuals attempting suicide, circulating copeptin concentrations, measured within the first hour of patient admission, were strongly correlated with both depression scores (r=0.63, P<0.001) [13] and anxiety scores (r=0.76, P<0.001) [13].…”
Section: Copeptin Mental Stress and The Pituitary-adrenal Axismentioning
confidence: 91%
See 3 more Smart Citations
“…In a further study, induction of panic symptoms in 30 healthy male human subjects by intravenous cholecystokinin-tetra peptide, a substance well known to induce panic symptoms and activate the pituitary-adrenal axis activity, resulted in substantial increases in circulating concentrations of copeptin and cortisol [37]. Further, children exposed to maltreatment, such as physical abuse, neglect, emotional maltreatment and sexual abuse, and individuals with suicidal behaviour have higher circulating copeptin concentrations [10,13]. Finally, although depressed ambulatory patients, participating in an exercise study, had similar plasma copeptin concentrations to controls [36], among individuals attempting suicide, circulating copeptin concentrations, measured within the first hour of patient admission, were strongly correlated with both depression scores (r=0.63, P<0.001) [13] and anxiety scores (r=0.76, P<0.001) [13].…”
Section: Copeptin Mental Stress and The Pituitary-adrenal Axismentioning
confidence: 91%
“…The notion that mental stress leads to higher circulating copeptin concentrations is supported by the medical literature, which also suggests the AVP-stimulated increased pituitaryadrenal axis activity could be involved [8]. In one study, 25 medical students were tested immediately prior to a written examination and after its conclusion [10] Comparing before and after, the students had higher heart rate, reported a higher stress level, and had higher serum concentrations of copeptin and cortisol after the study [10]. In another study, 20 healthy adults underwent the Trier Social Stress Test [11].…”
Section: Copeptin Mental Stress and The Pituitary-adrenal Axismentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, evidence has indicated that plasma copeptin levels are associated with psychosocial stress and HPA axis activation, without the main limitation of saliva cortisol measurements, such as the estimation of HPA activation only in a short time before assessment. In fact, copeptin levels seem to be altered even several months or years after the stressor . Although peripheral copeptin has been considered a promising biomarker, it was never measured in individuals with BD.…”
mentioning
confidence: 99%